Implementation of the alternative tourism paradigm in Bali Aga Traditional Village - Nyoman Dini Andiani; I Made Antara; Wayan Ardika; I Nyoman Sunarta (Journal of Applied Sciences in Travel and Hospitality, 2021)
The paradigm of developing alternative tourism is a development option for Bali Aga village as a tourism village. This paper aims at investigating form of alternative tourism implementation in Bali Aga Village valued by its tourist activities. This research focuses on tourist aspects including the importance of culture, motives for travelling (what they do on holiday and how they feel and behave) such as participating with the local people making bamboo weaving, they felt like family members. Because of the interaction that makes tourists and local people very closely filled with a sense of kinship. The importance of this research is to determine how much the characteristics of alternative tourism have been implemented in Bali Aga village. This research is a qualitative research. Data were taken by administering purposive sampling technique. The results of the study are used as a basis for describing the application of alternative tourism concepts in two villages of Bali Aga, namely Pedawa Village and Sidatapa Village, Buleleng Regency. The study shows that (1) tourists really like the culture that is owned by the community, (2) the purpose of visiting tourists does have a purpose to get to know the culture of the community and be involved in people's lives; (3) visiting tourists live in the home of the Bali Aga village community. Thus, the totality of community involvement as actors of tourist service providers has been able to show the main characteristics of alternative tourism.